PENINGKATAN KOMPETENSI PRAMUWISATA KAWASAN PERBATASAN NEGARA DI DESA WISATA TEMAJUK - Trisnawati, Hikmah; Fatihah, Nur Astri; Pahima (Yayasan Sagita Akademia Maju, 2024)
Temajuk Tourism Village in the tail of Kalimantan is one of the popular tourist destinations in West Kalimantan. The main tourist attraction in Temajuk Village is the beach. But apart from the beach, this village has many potential natural and cultural tourism attractions and has a strategic location because it borders Malaysia on land and at sea. The relatively increasing number of visits raises new problems, namely the lack of human resources for tour guide services that are able to provide satisfaction and memorable experiences for tourists. The purpose of this mentoring is to prepare local tour guide resources who are able to lead, guide, and tell stories to tourists either on a group or individual scale. This mentoring method uses experiential learning, which means that in addition to being given material, participants will also do simulations to get real experience. As a result, the resources of tour guides, which previously only came from Pokdarwis members, have now increased with the joining of youth organisation members. The ability to guide groups and tell stories to tourists has been obtained and participants are also able to make local tour packages.